STRATEGIES FOR TRANSLATING ENGLISH BUSINESS LEXICON INTO UZBEK: A COMPARATIVE ANALYSIS OF FINANCIAL AND MARKETING TERMS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores translation strategies applied to English business exical units in the Uzbek language context, focusing on financial and marketing terminology. By comparing examples from both domains, the study identifies patterns in the application of translation techniques such as borrowing, calque, literal translation, modulation, and adaptation. The analysis is based on a small corpus of authentic financial reports and marketing materials. Results reveal that financial terminology often requires calque and borrowing due to technical specificity, while marketing terms tend to involve modulation and cultural adaptation to preserve meaning and persuasive intent. The study underscores the need for a standardized bilingual glossary and further research into domain-specific translation strategies.